2013
DOI: 10.1007/978-3-642-40483-2_36
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physicality on Low Fidelity Interactive Prototyping for Design Practice

Abstract: Abstract. In this paper we propose the concept of 'active' and 'passive' physicality as mental models to help in understanding the role of low fidelity prototypes in the design process for computer embedded products. We define 'active physicality' as how the prototype and its software react to users and 'passive physicality' as how the prototype looks and feels offline. User trials of four different types of 'low fidelity' prototypes were undertaken using an existing product as the datum. Each prototype was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Often, the level of refinement, detail, and functionality of a prototype increases as designers develop a deeper understanding about the solution space and build on what they learned from earlier iterations (Ulrich and Eppinger 2015;Yang and Epstein 2005). Consequently, early prototypes do not always represent the quality and functionality of the intended end product, and stakeholders' perceptions of a new idea might potentially be negatively influenced by the nature and level of refinement of the prototype with which they are presented (Crilly et al 2004;Hare et al 2013;Lim et al 2006).…”
Section: Timing and Fidelity Of Prototypes In A Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, the level of refinement, detail, and functionality of a prototype increases as designers develop a deeper understanding about the solution space and build on what they learned from earlier iterations (Ulrich and Eppinger 2015;Yang and Epstein 2005). Consequently, early prototypes do not always represent the quality and functionality of the intended end product, and stakeholders' perceptions of a new idea might potentially be negatively influenced by the nature and level of refinement of the prototype with which they are presented (Crilly et al 2004;Hare et al 2013;Lim et al 2006).…”
Section: Timing and Fidelity Of Prototypes In A Design Processmentioning
confidence: 99%
“…Simply increasing presentation quality and functionality of a prototype, however, does not automatically lead to better input from stakeholders. Recent studies in the field of human-computer interaction concluded that a balance between quality and functionality of prototypes might be most beneficial for the collection of input from stakeholders (Hare et al 2013;Lim et al 2006). The authors further emphasized that the context surrounding the prototype feedback session, such as task scenarios, social and physical circumstances, as well as the participants themselves, can influence the type and quality of stakeholder input.…”
Section: Timing and Fidelity Of Prototypes In A Design Processmentioning
confidence: 99%
“…The data was analysed to elicit design recommendations for each prototype and these were compared to the final device (Hare, Gill, Loudon, & Lewis, 2013). Participants using the white model gave good feedback indicative of the final device.…”
Section: Results Of the User Trialmentioning
confidence: 99%
“…In this study, the technique used to construct the four prototypes was determined by our proposed definition of active and passive physicality (Hare, Gill, Loudon, & Lewis, 2013). The intention was to include the four permutations of active and passive physicality levels as demonstrated by each quadrant of Figure 1.…”
Section: Case Study 1 -Media Playermentioning
confidence: 99%